The Economic Approach to Public Policy : Selected Readings - Amacher, Ryan; Tollison, Robert D.; Willett, Thomas D. (Cornell University Press, 2019)
Can traditional economic theory help to solve today's vexing social problems? This unique collection of thirty-six papers strongly suggests that it can. The economic approach is applied imaginatively by the authors to a wide range of contemporary issues, such as crime, higher education, the environment, revenue sharing, equity, justice, and the distribution of income. The articles also deal with governmental behavior and the role of the economist as governmental adviser. Shaped during the preparation and teaching of college classes, the book is well suited for courses in principles of economics, microeconomics, price theory, and public policy development and analysis. It should also prove a useful reference work for policy makers.